CONCEPTUAL FRAMEWORK OF THE FORMATION OF FUTURE ELEMENTARY SCHOOL TEACHERS’ SUBJECT COMPETENCE IN THE STUDY OF ANATOMY AND PHYSIOLOGY - Mondich , Oksana (Educological discourse, 2020)
The paper provides theoretical and methodological foundations of the formation of future elementary school teachers’ subject competence in the study of anatomy and physiology as the basis for future elementary school teachers’ health protective activities, and application of health protecting technologies.